Estágios curriculares : óptica do egresso do curso de odontologia da Universidade Federal do Ceará - Lôbo, Alessandra Évellin D’Almeida (2013)
The Supervised Internship in Services of the Health System I, II and III are disciplines that integrate the curriculum of the course of Dentistry, Faculty of Pharmacy, Dentistry and Nursing on Federal University of Ceará (UFC) established in 2005. Occur in the 9th and 10th semesters of the course and follow the guidelines of the National Curriculum Guidelines, they aim to make students learn about the public health policies, forms of organization of services and practical actions at all levels of health care. Considering the time passed since the implementation of new curriculum and the need for continuous monitoring of this, a study was idealized to evaluate the internships from the perception of students who graduated from Dentistry at the UFC. Therefore, it was a descriptive and investigative study with qualitative approach through semi-structured interviews with former students of the UFC, formed in 2010. The aspects investigated were related to duration of stages, the infrastructure of local stage, the performance of supervisors, the correlation between the experiences and content studied during the course, the contribution of the stages for the formation of egress and their suggestions for improvement of them. The method recommended for data analysis was that described by Bardin - Content Analysis. The results were grouped into four categories as follows: Category 1 - The academic knowledge and reality, Category 2 - Performance of advisors, Category 3 - Infrastructure and Category 4 - Stage helped their career choice - which guided the discussions. It was concluded that despite the deficiencies reported on the infrastructure of the local stage, they contributed to the training of graduates, for they promoted a rapprochement with the social reality and the reality of health services. The role of the advisors was evaluated as positive, because assisted in the construction of new knowledge and practices, which were not contemplated during the disciplines intra-mural. The stages functioned as an opportunity to deepen the experience in some specialties, making the student chose this area for their professional practice, and also observed that the majority of respondents reported interest in future work in Public Health. Suggestions scored during the study will support the achievement of adjustments that are necessary to improve the curriculum, it is indispensable that other studies to avaluate the stages over time and who seek to investigate the opinions of others involved in the process: users, guiding stage and managers of health services.